(3aJGhi bGVj NGfs - (3bGVj NGf, MSf Hf efUhQ Hf CHj GdbGSe, J (B592 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd GdbGVj GdMSf Hf efUhQ Hf eMehO GdChRLfOj jbhd GdChRLfOj PcQJ aj gPG GdcJGH ef GdeSGFd GdJj jcKQ hbhYgG hJeS GdMGLI EdjgG s
(3BNQgG (B:s
(3cGf aJHWd ELGOI UGMH GdSajfI GdSajfI ef GdQGcH dCfg dGHO ddedGM ef Cf jchf aj GdSajfIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 224s
(3eYLe GdeDdajf (B1 / 594s
(3cTa GdXfhf (B2 / 1227s
(3TPQGJ GdPgH (B4 / 308s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs